Impact of Microfinance on Women Empowerment - Basnet, Surendra (KMC Journal, 2023)
In recent years, most microfinance programmes have focused on gender issues with significant support given to poor female clients to facilitate their access to capital. The study examines the impact of economic development, improvement in family matters, decision to use public amenities and political empowerment on women empowerment of participants in Surkhet district. The study followed the positivist research philosophy. The deductive approach, quantitative research method, and the descriptive and causal-comparative research design were applied to draw the study’s conclusion. 390 women participants were selected for the study using the convenience sampling method. The study is based on self-made questionnaires to the women taking microfinance services. The primary data were collected from household surveys and interview methods. The collected data were analyzed using SPSS and Amos graphics software. This study used descriptive and inferential statistics for data presentation and analysis. The hypotheses were tested through the SEM technique. The study’s findings show that economic development, improvement in family matters, decision to use public amenities, and political empowerment significantly impact women’s empowerment. Further, microfinance services and women empowerment have a significant relationship. The results of this study provide substantial implications for government and microfinance organizations to shape their plans for women’s empowerment.